Interfacial Reactivity of the Filled Skutterudite Smy(FexNi1−x)4Sb12 in Contact with Liquid In-Based Alloys and Sn - Giovanna Latronico; Fabrizio Valenza; Riccardo Carlini; Paolo Mele; Cristina Artini (Metals, 2020)
The study of the wettability of thermoelectric materials, as well as the search for the most proper brazing alloys, is of the maximum importance to get one step closer to the realization of a thermoelectric device. In this work, a wettability study of the filled skutterudite Smy(FexNi1−x)4Sb12 by Sn and In-based alloys is presented. Samples, having both p- and n- characters were prepared by the conventional melting-quenching-annealing technique and subsequently densified by spark plasma sintering (SPS). Afterward, wettability tests were performed by the sessile drop method at 773 K for 20 min. Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analyses performed on the cross-section of the solidified drops suggest quite a complicated scenario due to the coexistence and the interaction of a large number of different elements in each analyzed system. Indeed, the indication of a strong reaction of In-based alloys with skutterudite, accompanied by the formation of the InSb intermetallic compound, is clear; on the contrary, Sn exhibits a milder reactivity, and thus, a more promising behavior, being its appreciable wettability, whilst coupled to a limited reactivity.